Measuring entrepreneurship: Do established metrics capture high-impact Schumpeterian entrepreneurship? - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2019)
Are quantitative measures driven by small business activity also valid proxies for high-impact Schumpeterian entrepreneurship? We compile four hand-collected measures of high-impact Schumpeterian entrepreneurship (VC-funded IPOs, self-made billionaire entrepreneurs, unicorn start-ups, and young top global firms founded by individual entrepreneurs) and six measures dominated by small business activity as well as institutional and economic variables for 64 countries. Factor analysis reveals that much of the variation is accounted for by two distinct factors: one relating to high-impact Schumpeterian entrepreneurship and the other relating to small business activity. Except for the World Bank measure of firm registration of limited liability companies quantity-based measures tend to be inappropriate proxies for high-impact Schumpeterian entrepreneurship.
Keywords: L5; M13; O31; P14; 330; Billionaire entrepreneurs; High-impact entrepreneurship; Innovation; Institutions; Schumpeterian entrepreneurship; Self-employment